IMPROVING ENGLISH VOCABULARY PROFICIENCY THROUGH THE 'SAVE THE HANGMAN' GAME METHOD: A STUDY ON CLASS VIII B STUDENTS AT SMPN 11 PONTIANAK IN THE ACADEMIC YEAR 2022-2023 - Kurniawan, Dendy; Rosnija, Eni; Mekar, Susanty (JOEEL (Journal of English Education and Literature), 2024)
Improving English Vocabulary Proficiency by Using Save the Hangman Game Method to Students of Class VIII B in SMPN 11 Pontianak in Academic Year 2022-2023. This study aimed to enhance English vocabulary proficiency among eighth-grade students in Class VIII B at SMPN 11 Pontianak during the 2022-2023 academic year using the Hangman game method. It employed a Class Action Research approach, focusing on implementing the Save the Hangman game at SMPN 11 Pontianak. The research consisted of two cycles involving planning, action, observation, and reflection. Data collection instruments included observation sheets for student and teacher activities, vocabulary tests, and a questionnaire. The findings indicated a 7% increase in vocabulary skills from the first cycle (62%) to the second cycle (70%), reaching the passing criteria of a score above 61. The quality of teacher activity improved by 10%, from 64.52% in the first cycle to 74% in the second cycle. Additionally, student engagement in active learning increased by 14% for very active criteria (from 41% to 55%) and by 16% for active criteria (from 29% to 45%). However, the percentage of students considered active enough decreased by 5% (from 14% to 9%), and no students fell into the less active criteria in the second cycle.